The acute cardiovascular actions of intravenous thyrotrophin releasing hormone (TRH) in man are mediated by non-catecholaminergic mechanisms. - Bouloux, P; Corsello, S; Besser, M; Grossman, A (1996)
1. Intravenous bolus doses of thyrotrophin releasing hormone (TRH, 50-1000 micrograms) caused statistically significant, non-dose dependent and transient rises in blood pressure, heart rate and plasma catecholamines in healthy young males. 2. Mean peak incremental rises in systolic blood pressure (mean +/- s.e. mean) following 50, 200 and 500 micrograms TRH were 14.3 +/- 2.9 mmHg, 15.7 +/- 3.2 mmHg and 17.1 +/- 3.9 mmHg respectively (all P < 0.05 vs placebo). Mean incremental rises in heart rate for the three doses of TRH were 8.2 +/- 2.2 beats min-1, 7.1 +/- 1.8 beats min-1, and 10.7 +/- 2.9 beats min-1 respectively (all P < 0.05 vs placebo). 3. Following the 50 micrograms and 1000 micrograms doses of TRH, plasma noradrenaline and adrenaline rose significantly (P < 0.05) between 4 and 8 min. Mean +/- s.e. mean incremental plasma noradrenaline rise following 50, 200 and 100 micrograms TRH were 0.4 +/- 0.13 nmol 1(-1), 0.37 +/- 0.21 nmol 1(-1) and 0.41 +/- 0.18 nmol 1(-1) respectively. Mean +/- s.e. mean incremental rise in adrenaline for the 50, 200 and 1000 micrograms dose were 0.13 +/- 0.04 nmol 1(-), 0.08 +/- 0.03 nmol 1(-1), and 0.11 +/- 0.05 nmol 1(-1) respectively. 4. Following administration of the ganglion blocking drug pentolinium (5 mg) the incremental systolic blood pressure and heart rate rises following 500 micrograms TRH alone 16.6 +/- 2.8 mmHg and 10.4 + 3.1 beats min-1 respectively. 5. The rises in plasma noradrenaline and adrenaline following TRH were attenuated by prior ganglion blockade. 6. alpha-Adrenoceptor blockade with thymoxamine (0.3 mg kg-1 bolus + 0.3 mg kg-1 h-1 infusion), singly and combined with intravenous propranolol (10 mg i.v. over 10 min), did not alter the pressor or tachycardic effects of 500 micrograms TRH. 7. In conclusion, although plasma noradrenaline rises following i.v. TRH, suggesting activation of the sympathetic nervous system, this effect is not responsible for the pressor response to TRH, which appears to be due to either a direct vasoconstrictive effect on the peripheral resistance vessels or a direct inotropic/chronotropic effect on the heart.